2019
DOI: 10.1200/jco.2019.37.7_suppl.582
|View full text |Cite
|
Sign up to set email alerts
|

Are immune checkpoint inhibitors (ICI) a valid option for papillary renal cell carcinoma (pRCC)? A multicenter retrospective study.

Abstract: 582 Background: pRCC is the most common non-clear cell RCC (nccRCC) and represents up to 15% of RCC. Pivotal studies evaluating ICI mostly excluded nccRCC. Therefore the efficacy of ICI in pRCC remains to be demonstrated. Methods: We retrospectively investigated the activity and safety of PD-1/PD-L1 inhibitors (PD-1i) specifically in patients (pts) with metastatic pRCC from 15 centers in France and Belgium. Pts baseline characteristics, treatment outcome and safety were collected. Primary endpoint was time-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…No differences in the genetic mutations between responders and nonresponders were identified. Similar response rates (20%) were observed in another retrospective study with 41 NC-RCC patients who received nivolumab [33] and combination of CTLA4 (ipilimumab) [34,35]. In total, four prospective phase 2 trials, including primarily patients with pRCC, have been reported.…”
Section: 3supporting
confidence: 70%
“…No differences in the genetic mutations between responders and nonresponders were identified. Similar response rates (20%) were observed in another retrospective study with 41 NC-RCC patients who received nivolumab [33] and combination of CTLA4 (ipilimumab) [34,35]. In total, four prospective phase 2 trials, including primarily patients with pRCC, have been reported.…”
Section: 3supporting
confidence: 70%
“…Conversely, De Vries‐Brilland et al . only found a limited activity of anti‐PD‐1/PD‐L1 treatment (used as first‐ to third‐line and beyond) in their pRCC cohort . This emphasises the need for further detailed investigation of the immune microenvironment in a non‐ccRCC patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Among RCC types, most studies assessing efficacy of immune therapy have focused on ccRCC . Variable preliminary results on the performance of immune check‐point inhibitors in non‐ccRCC are forthcoming in two studies . McDermott et al .…”
Section: Discussionmentioning
confidence: 99%